Impact of photoperiods on the specific activities of immune and antioxidant enzymes in different tissues of Dybowski's frog (Rana dybowskii). Issue 11 (2nd November 2022) - Hu, Nan; Yu, Changyue; Jin, Jiaxin; Zhao, Xinmiao; Zhao, Yingying; Wei, Hua; Li, Yingdong
ABSTRACT: Many physiological activities in amphibians show rhythmic changes to adapt to ambient light conditions. However, the effects of photoperiod variation on the immune and antioxidant status and their possible correlation with different tissues have not been reported in Dybowski's frog, Rana dybowskii . In this study, the specific activities of immune and antioxidant enzymes in R. dybowskii under different photoperiods were evaluated. The results demonstrated that the photoperiod significantly impacted antioxidant enzymes and immune enzymes in Dybowski's frog. In terms of antioxidant enzyme activity, catalase (CAT) and superoxide dismutase (SOD) activities in frogs at 6 L:18D and 0 L:24D were significantly higher than those at 18 L:6D and 24 L:0D, respectively. Further, the activities of these enzymes increased during the dark phase and decreased during the light phase. The malondialdehyde (MDA) content decreased significantly with the decrease in photoperiod time. Lysozyme (LZM) activity in serum and the liver decreased with a prolonged photoperiod. LZM activity in the dark cycle was higher, but the peak activity in skin occurred at noon. Thus, long-term light exposure may cause oxidative stress in Dybowski's frog. Accordingly, a 6 L:18D photoperiod may be suitable for optimum physiological functions of this species.